Biomechanical support to a national swim program and research required to perform that service - Manson, B. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
Swimming is a difficult sport in which to research and carry out support services in biomechanics. It occurs at the intersection between air and water, limiting kinematic analysis because visual images are hidden by splashes and bubbles. There is also a difficulty in obtaining kinetic analysis as a consequence of an inability to use force transducers which require attachment between the surfaces experiencing the force. Swimming does however provide one real advantage in that there are primarily only three areas that are needed to analyse performance. These are in the start, turn and relay changeover area, in the free swimming area and in competition analysis. This paper details the application of biomechanical servicing and research systems in swimming at the Australian Institute of Sport.